Effects of riparian forest removal on the trophic dynamics of a Neotropical stream fish assemblage. Issue 1 (24th May 2016) - Lobón‐Cerviá, J.; Mazzoni, R.; Rezende, C. F.
Abstract : The effects of riparian forest removal on a neotropical stream fish assemblage were assessed in the Mata Atlântica. Fish assemblage structure and fish feeding patterns were quantified at three sites along a pristine‐to‐deforested gradient in a Serra do Mar stream: (1) a pristine site fully covered by canopy with no light penetration and transparent waters, (2) an intermediate site with partially removed forest and (3) a fully removed forest site with no canopy and full light penetration where siltation and turbid waters predominate. Fish assemblage structure, fish densities and their feeding patterns differed widely among sites. Whilst the same five fish species occurred at the three sites, forest removal favoured the occurrence of sediment‐tolerant iliophagous benthic species at the deforested site. At the pristine site, invertebrate prey predominated in water column fish diet and feeding overlap among species was low. Severe shifts in the feeding patterns were noticed in both deforested sites. Invertebrates were replaced by detritus, organic matter and algae at both sites and feeding overlap increased markedly. The overwhelming feeding adaptability of these neotropical fishes appeared capable of buffering the deleterious effects of forest removal on stream quality in terms of increased light penetration, siltation and water turbidity. Forest cutting in this Mata Atlântica stream clearly caused strong functional changes associated with forest clearance through important modifications in the assemblage organization and trophic patterns of the main species, but did not eliminate species.